Liberty Hyde Bailey : essential agrarian and environmental writings - Bailey, L. H. (Liberty Hyde), 1858-1954 (Cornell University Press, 2008)
This unique volume contains selected works of Liberty Hyde Bailey (1858-1954), a scholar-essayist-naturalist who espoused a "biocentric worldview." The work presents what the editor calls a "comprehensive introduction to Bailey's thinking on agriculture, nature, community, and education," drawn from ten of Bailey's most popular published works. The 42 excerpts or full essays are organized under nine descriptors that lay out Bailey's inimitable observations and agri-environmental (nature-minded) philosophical perspective, one that stands in contrast to the contemporary anthropocentric view